Effect of aqueous and alcoholic extracts of Ziziphora clinopodioides on apoptosis and alteration of caspase-3 and caspase-9 gene expression in anterior horn neurons of the spinal cord after sciatic nerve compression in male rats - Iman Abdolamir Abdolsamad Halaf; Maryam Tehranipour; Homa Mahmodzadeh Akharat (مجله دانشگاه علوم پزشکی بیرجند, 2021)
Background and Aim: Caspase family genes promote degeneration and are involved in apoptotic processes. The Ziziphora clinopodioides from the mint family (Lamiaceae) is one of the plants strong with anti-inflammatory effects and involved in the process of nervous system repair. The present study aimed to determine the effects of aqueous and alcoholic extracts of Ziziphora clinopodioides on apoptosis and alteration of caspase-3 and caspase-9 gene expression after sciatic nerve compression in male rats. Materials and Methods: In the present study, 24 male Wistar rats weighing 200-250 g were randomly assigned to four groups (n=6 in each group): control, compression, treatment with aqueous, and treatment with alcoholic extracts at a dose of 75 mg/kg. The extract was injected intraperitoneally on compression day and seven days later. After 28 days, samples were taken from the lumbar spinal cord subsequent to performing the perfusion method, and the samples were studied in two ways. Thereafter, in each group, total RNA was extracted from the lumbar spinal cord, cDNA was synthesized; subsequently, the expression changes in caspases-3 and caspases-9 were compared. Results: Based on the results, the number of neurons significantly decreased in the compression group, as compared to that in the control group, and demonstrated a significant increase in the aqueous extract group, in comparison with the compression group. Furthermore, the amount of caspases-3 and caspases-9 expression increased significantly in the compression group, compared to that in the control group. Moreover, caspase-3 and caspase-9 gene expression increased in the aqueous extract group, as compared to that in the compression group (P<0.001). Conclusion: It seems that the, the extract of Ziziphora clinopodioides has neuroprotective effects due to its antioxidant and anti-inflammatory properties, as well as phenolic and flavonoid compounds, such as pulegone.